Sextus Empiricus’ Outlines of Pyrrhonism in the Middle Ages - Wittwer, Roland (Vivarium, 2016)
This paper examines the authorship and reception of the medieval translation of Sextus Empiricus’ Outlines of Pyrrhonism. It is shown that its traditional ascription to Niccolò da Reggio (born ca. 1280) cannot be maintained, because the translation must have circulated already in the late 1270s. Its author is difficult to identify: the closest stylistic parallels are found with the anonymous translator of Aristotle’s De partibus animalium. With Alvaro of Oviedo († ca. 1282) and the otherwise unknown Johannes de Peretis two early readers can be named. Though a copy was accessible in Viterbo at this time and another copy possibly travelled around in Italy in the 1320s, no philosophical or other impact can be determined. A single reference is found in Peter of Auvergne’s Quaestiones-commentary on Aristotle’s Politics. Its origin is difficult to assess.